2018
DOI: 10.1016/j.jcrs.2018.01.010
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative analysis of corneal stromal riboflavin concentration without epithelial removal

Abstract: The system used in Group 1 produced corneal riboflavin concentrations that were theoretically adequate for effective transepithelial CXL (≥15 μg/g), while the system in Group 2 did not. Slitlamp grading successfully estimated the corneal riboflavin concentration and can be used to ensure an adequate concentration of riboflavin in the cornea for transepithelial CXL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…The failure rate of the standard epi-off CXL is known to be as high as 7.6%, especially in more advanced cases of ectasia. 12 In the current case, novel treatment with CK followed by non-invasive TE-CXL with a proprietary transepithelial riboflavin formulation and system 9 successfully treated advanced ectasia and stabilized the patient's vision without complications such as DLK.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The failure rate of the standard epi-off CXL is known to be as high as 7.6%, especially in more advanced cases of ectasia. 12 In the current case, novel treatment with CK followed by non-invasive TE-CXL with a proprietary transepithelial riboflavin formulation and system 9 successfully treated advanced ectasia and stabilized the patient's vision without complications such as DLK.…”
Section: Discussionmentioning
confidence: 83%
“…Two, TE-CXL can successfully treat ongoing postsurgical ectasia after epi-off CXL. We also suggest that effective TE-CXL 8 may, by avoiding surgical removal or disruption of the corneal epithelium, reduce the risk of DLK, infection, scarring and extended recovery that can occur as a result of epi-off CXL 6 , 9 in this situation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast to other methods of measuring stromal riboflavin concentration such as fluorescence imaging, slit-lamp examination, or high-performance liquid chromatography (HPLC), this method was able to provide a real-time measurement without relying on fluorescence measurements taken within the corneal stromal and produced comparative measurements to other techniques. 27,36,38,39 Mastropasqua et al 27 reported using iontophoresis and additives to achieve stromal riboflavin concentrations that were 21% and 44%, respectively, compared to the standard Dresden protocol using HPLC. Additionally, Cui et al 36 reported a peak stromal concentration of 50% standard measured via two-photon fluorescence after transepithelial BAK treatment.…”
Section: Measuring Stromal Rf Concentrationmentioning
confidence: 99%
“…The intact nature of the epithelium has been confirmed on slitlamp examination by an independent laboratory. 6 Next, in each subject a sponge-like loading device (CXL Ophthalmics), shaped to conform to the cornea's curvature (including steep, cone-shaped corneas) and maximize contact with the cornea was saturated with the riboflavin solution and placed over the entire cornea.…”
Section: Epithelium-on Corneal Cross-linking For Progressive Keratocomentioning
confidence: 99%